Direct and early complications of femoro-popliteal bypass in sequence of atheroscerosis treatment. - Kafa, Ali; Ahmad, Ghanem; Salloum, Mohammad (Latakia University Journal -Medical Sciences Series, 2018)
This study was carried out in AL-ASSAD and TISHREEN University Hospitals during the years 2010-2016, and included 116 patients with superficial femoral artery occlusion, and underwent femoro-popliteal bypass. Male: Female ratio was 4,7:1 , the peak incidence was in the 5th and 6th decades, The rate of our use of veins as a bypass was 19.83% of cases. The early bypass occlusion occurred in 6.03% of cases. the bypass infection occured in 2.58% of cases. 18 patients suffered from superficial wound infection 15.81%, postoperative hemorrhage in 4 patients with 3.44%. Mortality rate was 1.72% (2-myocardial infarction). Lymphatic complications occurred in 5 patients by 4.31%. The results were similar to universal studies. الإختلاطات المباشرة والقريبة التالية لإجراء المجازات الفخذية – المئبضية في سياق علاج الإنسداد الشرياني المزمن أُجريت الدراسة في مشفيي تشرين والأسد الجامعيين في مدينة اللاذقية، وشملت 116 مريضاً من المصابين بانسداد الشريان الفخذي السطحي, وتمّ قبولهم ومعالجتهم جراحياً عن طريق إجراء مجازة فخذية- مئبضية خلال الأعوام من 2010 إلى 2016 . وكانت نسبة إصابة الذكور إلى الإناث 4,7:1 مع ذروة حدوث في العقدين الخامس والسادس . كانت نسبة استعمالنا للوريد الذاتي كمجازات في الجراحة بنسبة19,83 % من الحالات. حدث انسداد المجازة الباكر بنسبة 6,03 % , إنتان المجازة بنسبة 2,58% , 18 مريضاً عانوا من إنتان الجرح بنسبة 15,51% , وحدث النزف بعد الجراحة عند 4 مرضى بنسبة 3,44% توفي مريضان بعد الجراحة نتيجة احتشاء عضلة قلبية وكانت نسبة هذا الإختلاط 1,72 %. وحدثت الإختلاطات اللمفية لدى 5 مرضى بنسبة 4,31 %. وكانت النتائج متقاربة مع الدراسات المقارنة.